A Novel Energy Proficient Computing Framework for Green Computing Using Sustainable Energy Sources - Ghulam Abbas; Mohammed Hatatah; Aamir Ali; Ezzeddine Touti; Ahmed Alshahir; Ali M. Elrashidi (IEEE Access, 2023)
Numerous green computing applications employ sustainable energy sources to abate redundant energy consumption. Renewable energy sources are vital to improving energy efficiency and should be used optimally. This paper introduces the Energy Proficient Computing Framework (EPCF) in the resource-centric cloud environment. The main objective of the EPCF is to improve the shared efficiency of energy distribution in the computing systems. Renewable energy is distributed among computers according to their running status and the number of calculations available. Traditional k-means clustering separates the states and computations when making this determination. This mapping procedure is repeated throughout the computation until the energy is dispersed without waste. Energy is conserved for the later use if the sources of the leak can be located in advance. As a result, we can conserve and use energy more effectively. In addition, it speeds up calculations and decreases service allocation waiting times. The proposed framework achieves 14.69% less energy cost for the different service al-location rates, 6.34% less energy drain, and 14.4% high efficiency.